"Full Rights" Feminists in South Asia: Freedom, Equality, and Justice. (April 2023) - Sen, Samita
Abstract: Histories of feminism in the past three decades have focused on the debate between equal rights and separate spheres, but have been less attentive to the many strands of socialist feminisms, which sought to build bridges between the women's movement and other social movements for freedom, equality and justice. Dorothy Sue Cobble addresses this gap, exploring the lives and works of social democratic women activists in relation to the equal rights versus separate rights debate. Reflecting the "global turn", Cobble explores many transnational connections. Picking up on these two themes – socialist feminism and global networks – I focus on the South Asian case.